Carcinoma of the Palate, Paraneoplastic Pleural Effusion; Case Report and Literature Review (Revista de Medicina Clinica, 2024)
Carcinomas of the soft palate are representative of just under 5-15% of oropharyngeal tumors; these in turn have been increasing due to the incidence of human papillomavirus (HPV) infection in recent years. Although their growth is slow and painless in the early stages, they later tend to be quite problematic and complicated to treat. Clinical case: 42-year-old male with diagnosis of acute respiratory failure type 1 + right pleural effusion + right lung metastases + left palate cancer cd20 negative, ki67 (3+), ck7 4+, poorly differentiated carcinoma type. Conclusions:Carcinoma of the palate is a rare entity among primary tumors. The authors at this hospital center have only treated one case in recent years; one of them is the one that is presented. The multidisciplinary treatment of the various medical specialties in whose treatment plays an essential role, as well as the various therapeutic modalities that have been discussed. There is a lack of consensus on the treatment of these tumors, in part due to the infrequency with which they occur.
Keywords: Carcinoma of the palate; Pleural effusion; Decortication